Ответ:
1) x²+10x+25=x²+2*x*5+5²=(x+5)²
2) x²-10x+25=x²-2*x*5+5²=(x-5)²
3) a²-8ax+16x²=a²-2*a*4x+4²x²=a²-2*a*4x+(4x)²=(a-4x)²
4) c²+8cx+16x²=c²+2*c*4x+4²x²=c²+2*c*4x+(4x)²=(c+4x)²
5) x²+4x+4=x²+2*x*2+2²=(x+2)²
6) a²+4ab+4b²=a²+2*a*2b+2²b²=a²+2*a*2b+(2b)²=(a+2b)²
7) b²-6b+9=b²-2*b*3+3²=(b-3)²
8) 1+6x+9x²=1²+2*1*3x+3²x²=1²+2*1*3x+(3x)²=(1+3x)²
9) 9a² -24 + 16b² = 3²a²-2*3a*4b+4²b²=(3a)²-2*3a*4b+(4b)²=(3a-4b)²
Пошаговое объяснение:
Надеюсь, я правильно поняла задачу.
Если что, * это умножение.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) x²+10x+25=x²+2*x*5+5²=(x+5)²
2) x²-10x+25=x²-2*x*5+5²=(x-5)²
3) a²-8ax+16x²=a²-2*a*4x+4²x²=a²-2*a*4x+(4x)²=(a-4x)²
4) c²+8cx+16x²=c²+2*c*4x+4²x²=c²+2*c*4x+(4x)²=(c+4x)²
5) x²+4x+4=x²+2*x*2+2²=(x+2)²
6) a²+4ab+4b²=a²+2*a*2b+2²b²=a²+2*a*2b+(2b)²=(a+2b)²
7) b²-6b+9=b²-2*b*3+3²=(b-3)²
8) 1+6x+9x²=1²+2*1*3x+3²x²=1²+2*1*3x+(3x)²=(1+3x)²
9) 9a² -24 + 16b² = 3²a²-2*3a*4b+4²b²=(3a)²-2*3a*4b+(4b)²=(3a-4b)²
Пошаговое объяснение:
Надеюсь, я правильно поняла задачу.
Если что, * это умножение.